The Greek Manosphere: The Case of the “No, You Are Not a Misogynist” Facebook Page - Angeliki Alipranti (Journalism and Media, 2025)
This research is driven by the expansion and popularity of the Manosphere network in the last decade, causing online and offline harassment of women. The study examines the phenomenon of the Manosphere in the Greek digital space and, more specifically, it researches the case of the popular, anonymous, and public accessed Facebook page of “Όχι, Δεν Είσαι Μισογύνης” (No, you are not a misogynist). The study’s research questions are whether the Greek Manosphere follows the same patterns of the international Manosphere groups and how gendered identities and roles are represented in its discourse. In order to answer the research questions, the study combines the method of thematic analysis and the approach of critical discourse analysis. The “Όχι, Δεν Είσαι Μισογύνης” (OΔΕΜ) page is found to be a case of the Men’s Rights Activists subculture of the Manosphere, with the main topic of interest being the online activism against feminism. Although the Facebook page reproduces traditional gender stereotypes and representations, a crucial difference from “classic” patriarchal perceptions is that the OΔΕΜ discourse portrays women as privileged, socially dominant and violent, while men are depicted as victims, discriminated by women and the social system. This inversion of reality is executed by the misinterpretation and falsification of data, along with the appropriation of activist and feminist discourse, which could lead to latent, or overt, misogynist perception and stereotypes (re)gaining popularity.